Physical, chemical, and biological methods for the removal of arsenic compounds - Lim, King Ting (Hindawi Publishing Corporation, 2014)
Arsenic is a toxic metalloid which is widely distributed in nature. It is normally present as arsenate under oxic conditions while arsenite is predominant under reducing condition. The major discharges of arsenic in the environment are mainly due to natural sources such as aquifers and anthropogenic sources. It is known that arsenite salts are more toxic than arsenate as it binds with vicinal thiols in pyruvate dehydrogenase while arsenate inhibits the oxidative phosphorylation process. The common mechanisms for arsenic detoxification are uptaken by phosphate transporters, aquaglyceroporins, and active extrusion system and reduced by arsenate reductases via dissimilatory reduction mechanism. Some species of autotrophic and heterotrophic microorganisms use arsenic oxyanions for their regeneration of energy. Certain species of microorganisms are able to use arsenate as their nutrient in respiratory process. Detoxification operons are a common form of arsenic resistance in microorganisms. Hence, the use of bioremediation could be an effective and economic way to reduce this pollutant from the environment.